Method for manufacturing a bonded body and method for manufacturing a ceramic circuit board

JP7933963B2Active Publication Date: 2026-10-13NITERRA MATERIALS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2025114410
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-10-07
Filing Date
2025-07-07
Publication Date
2026-10-13
Estimated Expiration
2041-10-07

Smart Images

  • Figure 0007933963000011
    Figure 0007933963000011
  • Figure 0007933963000012
    Figure 0007933963000012
  • Figure 0007933963000013
    Figure 0007933963000013
Patent Text Reader

Abstract

To provide a manufacturing method of a conjugate and a manufacturing method of a ceramic circuit board that can allow a compound with low solidification temperature or a phase change temperature to exist in a junction layer.SOLUTION: A manufacturing method according to an embodiment of the invention includes the steps of: preparing a joint brazing filler material that includes Cu, Ti, Sn or In, C; applying the joint brazing filler material paste to one of a ceramic substrate or a copper plate; arranging the other over the joint brazing filler material paste; and thermal bonding it to obtain a conjugate. In the thermal bonding step, a temperature rising rate is 30-100°C / min, a junction temperature is 750-1000°C, and a temperature dropping rate is 30-100. The obtained conjugate includes a junction layer. The junction layer includes a Ti reaction layer that includes titanium nitride or titanium oxide as the main component and plural first alloys that exist between the Ti reaction layer and the copper plate, include one or more selected from a Cu-Sn alloy and a Cu-In alloy, and have a Sn concentration or an In concentration being different from each other.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The embodiments described later relate to a method for manufacturing a bonded body and a method for manufacturing a ceramic circuit board. [Background technology]

[0002] A bonded structure of a ceramic substrate and a copper plate is used as a circuit board for mounting semiconductor elements and the like. International Publication No. 2018 / 021472 (Patent Document 1) discloses a ceramic copper circuit board in which a ceramic substrate and a copper plate are bonded. Patent Document 1 uses a brazing material containing Ag, Cu, Ti, etc. in the bonding layer. Patent Document 1 states that the bonding is 1 × 10⁻¹⁶ during bonding. -3 Heat bonding is performed under pressures below Pa. Such as 1 × 10 -3 Pressures below Pa are called vacuum. The joining method using Ti is called active metal joining. Because Ti is an active metal, it is easily nitrided or oxidized. In active metal joining, joining was performed in a vacuum to prevent nitriding or oxidation of Ti before joining. To join in a vacuum, the inside of the joining equipment had to be evacuated. Because heating required creating a vacuum, only batch processing was possible in the heating joining process. The heating joining process involved four steps per batch: vacuuming, heating, joining, and cooling. Each batch took more than 24 hours. Therefore, mass production was not feasible. On the other hand, International Publication No. 2018 / 199060 (Patent Document 2) discloses a heating and joining process performed in a continuous furnace. In the embodiment of Patent Document 2, joining is performed with a furnace length of 3m and a conveying speed of 10cm / min. Including the holding time in between, heating and joining can be completed in about 2 hours. [Prior art documents] [Patent Documents]

[0003] [Patent Document 1] International Publication No. 2018 / 021472 [Patent Document 2] International Publication No. 2018 / 199060 [Overview of the project] [Problems that the invention aims to solve]

[0004] Patent documents 1 and 2 use an Ag-Cu-Ti-based bonding brazing material containing 40% by mass or more of Ag. Ag and Cu are components that form a eutectic. The solidification temperature of the AgCu eutectic is approximately 780°C. The bonding temperature of the activated metal bonding method is 800°C to 950°C. Since the solidification temperature of the AgCu eutectic is approximately 780°C, solidification begins during the bonding process. In the bonding process, the bond is held at the bonding temperature and then cooled to room temperature. If the solidification temperature of the compounds present in the bonding layer is high, thermal stress increases during the cooling process. This increase in thermal stress led to an increase in the warping of the bonded body. To address these problems, the present invention provides a method for manufacturing a bonded body and a method for manufacturing a ceramic circuit board, which allows for the presence of compounds with low solidification temperatures or phase change temperatures in the bonding layer. [Means for solving the problem]

[0005] A method for manufacturing a bonded body according to an embodiment includes the step of preparing a bonding brazing material containing Cu, Ti, a first element selected from Sn and In (one or two of these elements), and C, with the total amount of these elements being 100 atomic%, Cu being 50 atomic% or more, Ti being 5 atomic% or more and 40 atomic% or less, the first element being 2 atomic% or more and 35 atomic% or less, and carbon being 0 atomic% or more and 12 atomic% or less. The manufacturing method includes the step of forming the bonding brazing material into a bonding brazing paste. The manufacturing method includes the step of applying the bonding brazing paste to the surface of a ceramic substrate or a copper plate. The manufacturing method includes the step of placing the copper plate or ceramic substrate on the bonding brazing paste. The manufacturing method includes a heating bonding step of heating the ceramic substrate and the copper plate to obtain a bonded body. In the heating bonding step, the heating rate is 30°C / min or more and 100°C / min or less, the bonding temperature is 750°C or more and 1000°C or less, and the cooling rate is 30°C / min or more and 100°C / min or less. The resulting bonded body comprises the ceramic substrate, the copper plate, and a bonding layer disposed between the ceramic substrate and the copper plate and formed by heating the bonding brazing paste. The bonding layer comprises a Ti reaction layer mainly composed of titanium nitride or titanium oxide, and a plurality of first alloys located between the Ti reaction layer and the copper plate, each containing one or more selected from Cu-Sn alloys and Cu-In alloys, and having different Sn or In concentrations from each other. [Brief explanation of the drawing]

[0006] [Figure 1] A schematic diagram showing an example of a joint according to the embodiment. [Figure 2] A schematic cross-sectional view showing an example of a bonding layer of a joint according to an embodiment. [Figure 3] A ternary phase diagram showing an example of the composition of a CuSnTi alloy. [Figure 4] A schematic diagram showing an example of a ceramic circuit board according to an embodiment. [Figure 5] A schematic diagram showing an example of a semiconductor device according to an embodiment. [Modes for carrying out the invention]

[0007] A method for manufacturing a joined body according to an embodiment includes a step of preparing a brazing filler metal for joining which contains 50 atomic% or more of Cu, 5 atomic% to 40 atomic% of Ti, 2 atomic% to 35 atomic% of a first element that is one or two elements selected from Sn and In, and 0 atomic% to 12 atomic% of C, when the total of Cu, Ti, the first element, and C is 100 atomic%. The manufacturing method includes a step of forming the brazing filler metal for joining into a brazing filler metal paste for joining. The manufacturing method includes a step of applying the brazing filler metal paste for joining to the surface of a ceramic substrate or a copper plate. The manufacturing method includes a step of disposing a copper plate or a ceramic substrate on the brazing filler metal paste for joining. The manufacturing method includes a heat joining step of heating and joining the ceramic substrate and the copper plate to obtain a joined body. In the heat joining step, the temperature rising rate is 30°C / min to 100°C / min, the joining temperature is 750°C to 1000°C, and the temperature lowering rate is 30°C / min to 100°C / min. The obtained joined body includes the ceramic substrate, the copper plate, and a joining layer that is disposed between the ceramic substrate and the copper plate and formed by heating the brazing filler metal paste for joining. The joining layer includes a Ti reaction layer containing titanium nitride or titanium oxide as a main component, and a plurality of first alloy layers located between the Ti reaction layer and the copper plate, each containing one or more selected from a Cu-Sn alloy and a Cu-In alloy, and having different Sn concentrations or In concentrations from each other. FIG. 1 is a schematic diagram illustrating an example of the joined body according to the embodiment. FIG. 2 is a schematic cross-sectional view illustrating an example of the joining layer of the joined body according to the embodiment. In FIG. 1 and FIG. 2, 1 denotes the joined body, 2 denotes the ceramic substrate, 3 denotes the copper plate, 4 denotes the joining layer, 5 denotes the Ti reaction layer, 6 denotes the first alloy, 7 denotes the second alloy, and 8 denotes the titanium silicide particles. In FIG. 2, the first alloy 6 is indicated by a dotted line. The second alloy 7 is indicated by dot hatching. The titanium silicide particles 8 are indicated by solid black filling. In the joined body 1 exemplified in FIG. 1, the copper plates 3 are respectively provided on both surfaces of the ceramic substrate 2 via the joining layers 4. Further, the vertical and horizontal dimensions of the ceramic substrate 2 are respectively the same as the vertical and horizontal dimensions of the copper plate 3. The joined body according to the embodiment is not limited to such a configuration. The joined body may have a structure in which the copper plate 3 is provided only on one surface of the ceramic substrate 2. The vertical and horizontal dimensions of the ceramic substrate 2 may be different from the vertical and horizontal dimensions of the copper plate 3.

[0008] Examples of the ceramic substrate 2 include a silicon nitride substrate, an aluminum nitride substrate, an aluminum oxide substrate, and an alumina-zirconia substrate. The alumina-zirconia substrate is a ceramic substrate obtained by mixing aluminum oxide and zirconium oxide. The thickness of the ceramic substrate 2 is preferably 0.1 mm or more and 1 mm or less. If the substrate thickness is less than 0.1 mm, the strength may decrease. If the substrate thickness is greater than 1 mm, the ceramic substrate acts as a thermal resistor, which may reduce the heat dissipation performance of the joined body. Further, the 3-point bending strength of the silicon nitride substrate is preferably 600 MPa or more. The thermal conductivity is preferably 80 W / m·K or more. By increasing the strength of the silicon nitride substrate, the substrate thickness can be reduced. For this reason, the 3-point bending strength of the silicon nitride substrate is preferably 600 MPa or more, and more preferably 700 MPa or more. The substrate thickness of the silicon nitride substrate can be reduced to 0.40 mm or less, and further to 0.30 mm or less. The 3-point bending strength of the aluminum nitride substrate is approximately 300 to 450 MPa. On the other hand, the thermal conductivity of the aluminum nitride substrate is 160 W / m·K or more. Since the strength of the aluminum nitride substrate is low, the substrate thickness is preferably 0.60 mm or more. The three-point bending strength of aluminum oxide substrates is approximately 300-450 MPa, and they are inexpensive. On the other hand, while the three-point bending strength of argil substrates is high at approximately 550 MPa, their thermal conductivity is only about 30-50 W / m·K. The ceramic substrate 2 is preferably either a silicon nitride substrate or an aluminum nitride substrate. Both the silicon nitride substrate and the aluminum nitride substrate are nitride ceramic substrates. Nitride ceramics react with an active metal brazing material containing Ti to form a reaction layer mainly composed of titanium nitride. Oxide ceramics also react with an active metal brazing material containing Ti to form a reaction layer mainly composed of titanium oxide. Oxide ceramics include aluminum oxide substrates and argil substrates. The Ti reaction layer 5 is a layer mainly composed of titanium nitride or titanium oxide. The layer mainly composed of titanium nitride or titanium oxide is formed by the reaction of the ceramic substrate 2 with the Ti in the active metal brazing material.

[0009] It is preferable that copper plates 3 are placed on both sides of the ceramic substrate 2. By joining copper plates to both sides, warping of the joined body can be suppressed. Pure copper plates or copper alloy plates can be used as copper plates 3. It is preferable that the copper plates 3 are oxygen-free copper. As indicated in JIS-H-3100 (ISO1337, etc.), the copper purity of oxygen-free copper is 99.96% by mass or higher. Oxygen-free copper is a type of pure copper. The copper plates 3 are used as circuit parts or heat sinks. By increasing the thickness of the copper plates 3, the current capacity and heat dissipation can be improved. For this reason, the thickness of the copper plates 3 is preferably 0.6 mm or more, and more preferably 0.8 mm or more.

[0010] The bonding layer 4 includes a Ti reaction layer 5 mainly composed of titanium nitride or titanium oxide. The Ti reaction layer 5 is formed when a so-called active metal bonding method is used. When the ceramic substrate 2 is a nitride-based ceramic, the main component of the Ti reaction layer 5 is titanium nitride (TiN). The titanium nitride, which is the main component of the Ti reaction layer 5, may contain compounds with an atomic ratio of titanium to nitrogen other than 1:1. When the ceramic substrate 2 is an oxide-based ceramic, the main component of the Ti reaction layer 5 is titanium oxide (TiO2). The titanium oxide, which is the main component of the Ti reaction layer 5, may contain compounds with an atomic ratio of titanium to oxygen other than 1:2, such as TiO2, TiO, and Ti2O3. The Ti reaction layer 5 refers to a region on the surface of the ceramic substrate 2 with a Ti content of 50% by mass or more. Furthermore, it is preferable that the Ti reaction layer 5 is present on the surface of the ceramic substrate 2 in an area of ​​40% to 100% per 200 μm unit length. 40% or more per 200 μm unit length means that, when observing the cross-section of the bonding layer 4, the Ti reaction layer 5 is formed on a total area of ​​40 μm or more out of 200 μm on the surface of the ceramic substrate 2.

[0011] The bonding layer 4 contains multiple first alloys 6 located between the Ti reaction layer 5 and the copper plate 3. The composition ratios of the multiple first alloys 6 are different from each other. Specifically, the multiple first alloys 6 have different Sn or In concentrations. Each of the multiple first alloys contains one or more selected from Cu-Sn alloys and Cu-In alloys. Note that not all Cu-Sn alloys or Cu-In alloys present in the bonding layer 4 need to have different Sn or In concentrations. It is sufficient for two or more first alloys 6 with different Sn or In concentrations to be present in the bonding layer 4. Below, we will mainly describe an example in which the first alloys 6 are Cu-Sn compounds. In the following example, it is also possible to replace the Cu-Sn compound with a Cu-In compound. Note that "different Sn concentrations" means that when the sum of the Cu content and Sn content is set to 100 atomic%, the Sn concentrations differ by 2 atomic percent or more. "Different In concentrations" means that when the sum of the Cu content and In content is set to 100 atomic%, the In concentrations differ by 2 atomic percent or more. The atomic ratio of Cu to Sn can be measured by point analysis using energy-dispersive X-ray spectroscopy (EDX). EDX is sometimes called EDS. Here, we will use SEM-EDX. A Field Emission SEM (FE-SEM) may also be used as the SEM. For the FE-SEM, a JEOL JSM-7200F or an instrument with equivalent performance will be used. For the EDX, a JEOL EX-74600U4L2Q or an instrument with equivalent performance will be used. FE-SEM observes the cross-section of the bonding layer 4. The cross-section is a plane parallel to the thickness direction. The thickness direction is perpendicular to the surface of the ceramic substrate 2 and parallel to the direction connecting the ceramic substrate 2 and the copper plate 3. The FE-SEM measurement conditions are set to an acceleration voltage of 15kV and a magnification of 3000x. The field of view is set to the thickness of the bonding layer × width direction of 40μm. The width direction is parallel to the surface of the ceramic substrate 2 and perpendicular to the thickness direction. The EDX measurement conditions are set to 50 scans and a duel time of 0.2ms. Duel time is the measurement speed per pixel. When performing area analysis with EDX, the acquisition pixel count is set to 256 horizontally x 198 vertically, the detection count to 3700-4100 cps (Count Per Second), and the quantitative map to 5 x 5 bits / point. Point analysis is an analysis using the results of a single detection count (one location). Area analysis is an analysis using the results of measurements with multiple detection counts. Area analysis is also sometimes called surface analysis. EDX analysis may be performed after first identifying the elements constituting the bonding layer and clarifying the specific elements. For example, if Cu (copper), Sn (tin), Ti (titanium), Si (silicon), O (oxygen), and N (nitrogen) are detected as elements constituting the bonding layer, these elements are designated as specific elements. By mapping the specific elements using the results of area analysis, the area ratio can be determined. If the thickness of the bonding layer is 30 μm, the field of view will be 30 μm in the thickness direction × 40 μm in the width direction. For SEM-EDX mapping, use the functions included with the SEM-EDX. If the mapping function is not included, use image processing software for mapping. The area ratio is calculated by performing EDX area analysis on three regions and using the average value. The area of ​​one region (field of view area) is 40 μm in the width direction multiplied by the thickness of the bonding layer. The measurement field of view is aligned with the bonding layer 4. Three arbitrary adjacent regions are analyzed from the cross-section of the bonding layer 4. The bonding layer 4 extends from the boundary between the ceramic substrate 2 and the bonding layer 4 to the boundary between the bonding layer 4 and the copper plate 3. The boundary between the ceramic substrate 2 and the bonding layer 4 is the bonding interface between the surface of the ceramic substrate 2 and the Ti reaction layer 5. For example, when a silicon nitride substrate is used, the bonding interface between the silicon nitride substrate and the titanium nitride layer is the boundary between the ceramic substrate 2 and the bonding layer 4. For example, the dashed line BL1 shown in Figure 2 is the boundary between the ceramic substrate 2 and the bonding layer 4. The boundary between the bonding layer 4 and the copper plate 3 is defined based on the amount of Ti. Near the boundary between the bonding layer 4 and the copper plate 3, the amount of Ti decreases from the bonding layer 4 toward the surface of the copper plate 3. The boundary is defined based on the location where a region with a Ti amount of 1 atomic percent or less is formed continuously for 50 μm in the width direction. If there are multiple such locations, the boundary between the bonding layer 4 and the copper plate 3 is defined based on the location closest to the bonding layer 4 (ceramic substrate 2) among the multiple locations. In Figure 2, the solid line SL between the bonding layer 4 and the copper plate 3 represents a set of points with a Ti amount of 1 atomic percent. As an example, near the solid line SL, in portions P1 and P2, regions with a Ti amount of 1 atomic percent or less are formed continuously for 50 μm in the width direction. Portion P1 is located closer to the ceramic substrate 2 than portion P2. Therefore, the dashed line BL2, based on portion P1, is defined as the boundary between the bonding layer 4 and the copper plate 3. EDX point analysis is used to measure the amount of Ti at the boundary between the bonding layer 4 and the copper plate 3. Point analysis is performed at 5 μm intervals to determine the amount of Ti. In addition, the region with a Ti amount of 1 atomic percent or less also includes the region with a Ti amount of 0 atomic percent (below the detection limit). The first alloy 6 refers to an alloy in which, when the total of Cu, the first element, and Ti is set to 100 atomic percent, the sum of Cu and the first element is 50 atomic percent or more. The first element is one or two selected from Sn and In. For example, for a Cu-Sn alloy, when the total of Cu, Sn, and Ti is set to 100 atomic percent, the sum of Cu and Sn is 50 atomic percent or more. For a Cu-In alloy, when the total of Cu, In, and Ti is set to 100 atomic percent, the sum of Cu and In is 50 atomic percent or more. The composition of the first alloy 6 is determined by EDX point analysis. The second alloy 7 refers to an alloy in which, when the total of Cu, the first element, and Ti is set to 100 atomic percent, the total of Ti and the first element is 50 atomic percent or more. For example, for a Ti-Sn alloy, when the total of Cu, Sn, and Ti is set to 100 atomic percent, the total of Ti and Sn is 50 atomic percent or more. For a Ti-In alloy, when the total of Cu, In, and Ti is set to 100 atomic percent, the total of Ti and In is 50 atomic percent or more. The composition of the second alloy 7 is determined by EDX point analysis. The Cu-Sn alloy may have a state in which Cu and Sn are mixed, or it may contain a compound of Cu and Sn. The compound may include intermetallic compounds. The Cu-Sn alloy may also have Ti mixed in or in a solid solution state. The first alloy 6 includes alloys with a melting point of 400°C or higher and 600°C or lower. The melting point of alloy 6 can be determined from the solidification point of the alloy. The solidification point is the temperature at which a liquid becomes a solid. In other words, it is the temperature at which the joining brazing material melts into a liquid phase and then cools to become a solid. For simplicity, the solidification point of the compound can be determined using a phase diagram. Alternatively, the joining layer 4 can be cut from the joined body 1 and gradually heated to measure the melting point.

[0012] The melting point of alloy 6 can be measured from the DSC curve. The DSC curve is the result of applying heat to a sample using a differential scanning calorimeter (DSC) and measuring the presence or absence of endothermic and exothermic reactions. When an endothermic or exothermic reaction occurs, a peak appears on the DSC curve. A peak in the negative direction indicates the occurrence of an endothermic reaction. A peak in the positive direction indicates the occurrence of an exothermic reaction. An endothermic reaction indicates that the sample is melting, decomposing, etc. An exothermic reaction indicates that the constituent elements of the sample are reacting with each other to form a compound (including alloys) or solidify. The larger the peak, the greater the heat of reaction. Here, a peak in the negative direction is called an endothermic peak, and a peak in the positive direction is called an exothermic peak. The peak's highest point is called the peak top. The difference between the peak's maximum and minimum points is called the peak height.

[0013] For example, since the endothermic peak is a peak in the negative direction, the DSC curve goes down and then up near the endothermic peak. Near the endothermic peak, the DSC curve shows a maximum point → minimum point → maximum point. This minimum point (the point where the value drops the lowest in the negative direction) is the peak top. Of the maximum points on the low-temperature and high-temperature sides of the minimum point, the one with the larger value is taken as the maximum maximum point (the point where the value rises the highest in the positive direction). The peak height is the value obtained by subtracting the minimum point from the maximum maximum point. Since the exothermic peak is a peak in the positive direction, the DSC curve rises and falls near the exothermic peak. Near the exothermic peak, a sequence of local minimums → local maximums → local minimums appears on the DSC curve. This local maximum (the point where the curve rises the highest in the positive direction) is the peak top. Of the local minimums on the low-temperature and high-temperature sides of the local maximum, the smaller value is defined as the minimum (the point where the curve falls the lowest in the negative direction). The peak height is the value obtained by subtracting the minimum from the local maximum. Note that the endpoint of an endothermic peak (a peak in the negative direction) may sometimes appear as an exothermic peak (a peak in the positive direction). Here, that endpoint is also counted as an exothermic peak. Alternatively, a baseline can be drawn to determine the height of each peak. Furthermore, in the DSC curve, changes of 0.02 mW / mg or more on the vertical axis are counted as peaks. In other words, changes of less than 0.02 mW / mg are not counted as peaks.

[0014] In the DSC curve during the cooling process, it is preferable to detect an exothermic peak in the range between 600°C and 900°C. The exothermic peak within this range represents the main component of the solidification reaction. Furthermore, it is preferable to have an exothermic peak in the range between 400°C and 600°C. As mentioned above, an exothermic reaction indicates that the brazing material components are reacting with each other to form compounds (including alloys) or that solidification is occurring. In other words, an exothermic peak in the range between 400°C and 600°C indicates that compound formation or solidification is occurring within that temperature range. Solidification is a reaction that involves a phase change from liquid to solid. Compound formation may also involve a phase change from a solid to a solid with a different crystal structure. By causing such phase changes in multiple stages, stress during cooling can be relieved. With the brazing material composition described later, the phase changes necessary for compound formation are the main factor in generating the exothermic peak. In other words, the presence of the first alloy 6 allows for the generation of an exothermic peak in the DSC curve between 400°C and 600°C during the cooling process. The presence of exothermic peaks in the ranges of 400°C to 600°C and 600°C to 900°C allows for multi-stage reactions involving phase changes. Here, the temperature at which a phase change from liquid to solid occurs is called the freezing point. The temperature at which a phase change to a solid with a different crystalline structure occurs is called the phase change point. Furthermore, if multiple alloys (including compounds) with different compositional ratios exist, their exothermic peaks may overlap. In other words, even if only one exothermic peak is detected, multiple alloys (including compounds) with different compositional ratios may still exist. The freezing point is the temperature at which a liquid phase changes to a solid phase. The phase change point is the temperature at which a solid changes to one with a different crystalline structure. By solidifying or undergoing a phase change within the range of 400°C to 600°C, the temperature at which thermal stress occurs can be lowered. The freezing point of conventional AgCu eutectic compounds is approximately 780°C. In the cooling process, the compound, which solidified at 780°C, generates thermal stress as it returns to room temperature. The existence of alloy 6, whose freezing point or phase change point is within the range of 400°C to 600°C, reduces the thermal stress that occurs after solidification or phase change at 400°C to 600°C until it returns to room temperature. Multiple alloys 6 have different composition ratios, and therefore their solidification points or phase transition points also differ. Multiple alloys 6 with different solidification points or phase transition points exist within the range of 400°C to 600°C. This allows for multi-stage solidification or phase transition of the bonded layer. This further reduces thermal stress. Thermal stress occurs during the process in which the bonding brazing material melts into a liquid phase, solidifies, and cools to room temperature. In particular, it is important to reduce the thermal stress from solidification to cooling to room temperature. By allowing the solidification or phase transition of alloy 6 to occur in multiple stages, the thermal stress from solidification to cooling to room temperature can be reduced. If the solidification point or phase transition point of alloy 6 is below 400°C, the solidification point or phase transition point of the bonded layer 4 will decrease, potentially degrading the temperature cycle test (TCT) characteristics. If the solidification point or phase transition point of alloy 6 is high, exceeding 600°C, thermal stress may increase. Therefore, the solidification point or phase change point of the first alloy 6 is preferably 400°C to 600°C, and more preferably 450°C to 550°C. Furthermore, even if the exothermic peaks in the DSC curve between 400°C and 600°C during the cooling process overlap, the effect of multi-stage solidification or phase change can be obtained by having multiple first alloy 6 with different composition ratios.

[0015] Furthermore, the first alloy 6 preferably contains one or more compounds selected from Cu-Sn compounds and Cu-In compounds. In compounds, the constituent elements are bonded at the atomic level. Examples of compounds include intermetallic compounds. Examples of alloys include solid solutions and eutectic alloys. Compounds are distinguished from solid solutions and eutectic alloys. The phase structure can be determined by the crystal structure and composition. For example, in a CuSn binary alloy, if the amount of Sn is 9 atomic percent or less, the alloy is mainly a solid solution. If the amount of Sn is 10 atomic percent or more, the alloy is more likely to form intermetallic compounds. It is preferable that at least a portion of the multiple first alloy 6s have a Sn content in the range of 3 atomic% to 30 atomic%. When the Sn content is in the range of 3 atomic% to 30 atomic%, it is easier to control the freezing point or phase transition point. If the Sn content is less than 3 atomic%, the freezing point or phase transition point will not drop sufficiently. Also, if the Sn content exceeds 30 atomic%, the freezing point or phase transition point may drop too low. For this reason, a Sn content of 3 atomic% to 30 atomic% is preferable. Furthermore, first alloy 6 with a Sn content of 3 atomic% to 30 atomic% is more likely to form Cu-Sn compounds. When EDX point analysis is performed on a region of Cu-Sn alloy with a high Cu content, it is preferable that more than 80% of that region consists of Cu-Sn alloys with a Sn content of 3 atomic% to 30 atomic%. EDX point analysis should be performed 10 or more times. A region with a high Cu content refers to a region where Cu is more abundant when comparing the atomic percentage of Cu with the atomic percentage of Ti, as determined by EDX area analysis.

[0016] Furthermore, the first alloy 6 may contain 2 atomic percent or less of metallic components other than Cu and Sn. These metallic components other than Cu and Sn are metallic components or impurities that constitute the brazing material. Examples of components of the brazing material other than Cu and Sn include Ti (titanium) and C (carbon), as will be described later. For example, the freezing point of TiSn alloy exceeds 600°C. If the amount of Ti in the Cu-Sn alloy increases, the freezing point or phase change point may not fall within the range of 400°C to 600°C. For this reason, it is preferable that the amount of Ti in at least some of the multiple first alloy 6s is 2 atomic percent or less, and more preferably 1 atomic percent or less. EDX point analysis is used to measure the amount of Ti in the Cu-Sn compound. Examples of components other than metallic components include oxygen and nitrogen. The first alloy 6 may contain 10 atomic percent or less of components other than Cu, Sn, and metallic components. Adding Ag to the brazing material makes it easier for AgCu eutectic to form. The melting point of AgCu eutectic is approximately 780°C. For this reason, it is preferable that the brazing material does not contain Ag as a component. In other words, it is preferable that the bonding layer 4 does not contain Ag. Sometimes, Ag-Cu-Sn-Ti, in which Ag is the main component, is used as the brazing material. If Ag is the main component, AgCu or AgSn will be formed. This reduces the proportion of CuSn alloy contained in the bonding layer 4. Therefore, the possibility of forming Cu-Sn alloys with different compositions decreases. From this point of view as well, it is preferable that the bonding layer 4 does not contain Ag.

[0017] Preferably, a portion of the plurality of first alloys 6 is a Cu-Sn alloy with a Sn content of 3 atomic% to 9 atomic% and another portion of the plurality of first alloys 6 is a Cu-Sn alloy with a Sn content of 10 atomic% to 30 atomic%. Here, a Cu-Sn alloy with a Sn content of 3 atomic% to 9 atomic% is referred to as the first Cu-Sn alloy, and a Cu-Sn alloy with a Sn content of 10 atomic% to 30 atomic% is referred to as the second Cu-Sn alloy. The first Cu-Sn alloy is preferably a Cu-Sn compound. The second Cu-Sn alloy is also preferably a Cu-Sn compound. This is because compound materials are more likely to undergo multi-step solidification or phase changes. The bonding layer 4 preferably contains a second alloy 7. The second alloy 7 contains one or two selected from Ti-Sn alloys and Ti-In alloys. The Ti-Sn alloy or Ti-In alloy may contain intermetallic compounds. For example, the intermetallic compound of the Ti-Sn alloy may be one or more selected from SnTi3, Sn3Ti5, and Sn5Ti6. In the average value measured at three locations on the bonding layer 4, it is preferable that the total area of ​​multiple first alloys 6 is greater than the total area of ​​the second alloy 7. That is, it is preferable that the total area of ​​the Cu-Sn alloy or Cu-In alloy is greater than the total area of ​​the Ti-Sn alloy or Ti-In alloy. The field of view is set to 40 μm in the thickness × width direction of the bonding layer. Measurements in one field of view may be performed in multiple steps. When measuring in multiple steps, each area should be set so as not to overlap with each other. Furthermore, it is preferable that at least a portion of the Cu-Sn alloy and the Ti-Sn alloy detected by EDX point analysis of the bonding layer 4 fall within the region enclosed by (97,3,0), (60,40,0), (2,40,58), and (39,3,58) in the Cu,Sn,Ti ternary phase diagram. Here, this region is referred to as the first composition region. Figure 3 is a ternary phase diagram of Cu, Sn, and Ti. In Figure 3, the concentration of each element is shown in atomic percent. First, image data is obtained by elemental mapping using the area analysis function of the SEM-EDX. The mapping function then performs EDX point analysis on areas identified as the first alloy 6 and the second alloy 7. Elemental mapping allows for the representation of differences in the concentration of specific elements using brightness. Areas with high concentration have high brightness, while areas with low concentration have low brightness. For example, by specifying Ti as the specific element, the concentration variations of Ti can be visualized. This function allows for the identification of the first alloy 6 and the second alloy 7 within the field of view. Specifically, by specifying the first element as the specific element and visualizing the concentration of these elements, the first alloy 6 within the field of view can be identified. Similarly, by specifying Ti as the specific element and visualizing the concentration of these elements, the second alloy 7 within the field of view can be identified. When EDX point analysis is performed on areas identified as the first alloy 6 and the second alloy 7, it is preferable that the composition falls within the first composition region. While alloys outside the first composition region may exist, having the alloy composition within the first composition region improves its properties. More preferably, when EDX point analysis is performed, at least a portion of the composition of the Cu-Sn alloy lies within the region enclosed by (97,3,0), (77,23,0), (52,23,25), and (72,3,25) in the Cu,Sn,Ti ternary phase diagram. This region is called the second composition region. The bonding layer 4 may contain the first alloy 6 having a composition outside the second composition region. On the other hand, if there is a large amount of the first alloy 6 having a composition within the second composition region, the properties can be further improved. Furthermore, when observing the Cu-Sn alloy by elemental mapping based on SEM-EDX area analysis and performing EDX point analysis on the Cu-Sn alloy, it is preferable that 80% or more of the analyzed locations have a composition within the range of the second composition region. Note that in EDX point analysis, 10 or more points are analyzed at locations that are at least 3 μm apart from each other. The Ti-Sn alloy detected by EDX point analysis of the bonding layer 4 is preferably within the region enclosed by (41,23,36), (24,40,36), (2,40,58), and (19,23,58) in the Cu,Sn,Ti ternary phase diagram. This region is called the third composition region. If the bonding layer 4 contains multiple Ti-Sn alloys, it is sufficient that the composition of at least some of the multiple Ti-Sn alloys is within the range of the third composition region. On the other hand, if there are many Ti-Sn alloys with compositions within the range of the third composition region, the properties can be further improved. Furthermore, when observing the Ti-Sn alloy by elemental mapping based on SEM-EDX area analysis and performing EDX point analysis on that Ti-Sn alloy, it is preferable that 80% or more of the analyzed locations have compositions within the range of the third composition region. Note that in EDX point analysis, 10 or more points are analyzed at locations that are at least 3 μm apart from each other.

[0018] The Ti reaction layer 5 preferably contains titanium nitride particles with an average particle size of 50 nm or less. Furthermore, it is preferable that Cu and a first element are present at the grain boundaries of these titanium nitride particles. The size of the titanium nitride particles in the Ti reaction layer 5 is analyzed using a scanning transmission electron microscope (STEM). A magnified image of the cross-section of the bonding layer is obtained using STEM. The particle size is defined as the distance between the two furthest points on the outer edge of the titanium nitride particles visible in the magnified image. The particle size is measured for any 30 particles. The average value of these measurements is defined as the average particle size. A small average particle size of 50 nm or less makes it easier for Cu and the first element to penetrate the grain boundaries. The presence of Cu and the first element at the grain boundaries of the titanium nitride particles allows for the solidification or phase change of the bonding layer 4 to occur in multiple stages.

[0019] The amount of Cu in the Ti reaction layer 5 is preferably within the range of 0.5 atomic% to 5 atomic%. When the amount of Cu in the Ti reaction layer 5 is within this range, thermal stress can be reduced without reducing the bonding strength. If the amount of Cu in the Ti reaction layer 5 is less than 0.5 atomic%, the amount of Cu may be too low, and the effect of reducing thermal stress may not be sufficiently obtained. If the amount of Cu is more than 5 atomic%, the strength of the Ti reaction layer 5 may be insufficient, and the bonding strength may decrease. The amount of the first element in the Ti reaction layer 5 is preferably between 0.05 atomic% and 2 atomic%. When the amount of the first element in the Ti reaction layer 5 is within this range, thermal stress can be reduced without decreasing the bonding strength. In addition, Cu and Sn in the Ti reaction layer 5 are easily alloyed. The formation of an alloy (preferably a compound) of Cu and Sn in the Ti reaction layer 5 suppresses the generation of thermal stress. The amounts of Cu and the first element in the Ti reaction layer 5 refer to the amounts present at the grain boundaries of the titanium nitride particles. Both TiN and Ti2N may be present as titanium nitride in the Ti reaction layer 5. The presence of both TiN and Ti2N allows for the solidification of the titanium nitride-based layer to occur in multiple stages. The thickness of the Ti reaction layer 5 is preferably 1 μm or less. More preferably, the thickness of the Ti reaction layer 5 is 0.3 μm or less. By making the Ti reaction layer 5 thin, it is possible to easily introduce Cu and the first element at the grain boundaries. Furthermore, the thickness of the Ti reaction layer 5 can be determined by transmission electron microscopy (TEM). The thickness of the Ti reaction layer 5 is measured relative to the interface between the Ti reaction layer 5 and the ceramic substrate. TEM-EDX is used for compositional analysis of the Ti reaction layer 5.

[0020] In the average value obtained by EDX area analysis of the three regions of the bonded layer 4, the total area of ​​the first alloy 6 is preferably 50% to 95% of the total area of ​​the three regions. The field of view area (size of one region) is set to 40 μm in the bonded layer thickness × width direction. When the total area ratio of the Cu-Sn alloy is within the range of 50% to 95%, the thermal stress of the bonded layer 4 can be reduced. If the total area ratio of the Cu-Sn alloy is less than 50%, the proportion of Cu-Sn alloy is small, and the effect of reducing thermal stress may be insufficient. Also, if the total area ratio of the Cu-Sn alloy is higher than 95%, the freezing point or phase change point of the bonded layer 4 may be lowered too much. If the freezing point or phase change point of the bonded layer 4 is lowered, the TCT properties of the bonded body 1 may be reduced. For this reason, the total area ratio of the Cu-Sn alloy is preferably 50% to 95%, and more preferably 70% to 90%. Furthermore, it is preferable that the total area of ​​the Cu-Sn alloy is within the range of 50% to 95% regardless of which three regions in the bonding layer 4 are measured. In the average value obtained by EDX area analysis of the three regions of bonding layer 4, the total area of ​​the Ti-Sn alloy is preferably within the range of 5% to 30% of the total area of ​​the three regions. The total area of ​​the titanium silicide is preferably within the range of 0.5% to 15% of the total area of ​​the three regions. Furthermore, the area ratio of other materials is preferably within the range of 10% or less. Other material structures include the Ti reaction layer and carbides. In the measurement of the area ratio, the area analysis function of SEM-EDX is used to obtain image data by element mapping. The mapping function attached to the area analysis function of SEM-EDX is used. If no mapping function is available, an electron probe microanalyzer (EPMA) may be used. Further, the image data obtained by SEM-EDX may be processed using image analysis software. As the image analysis software, Image-J or equivalent software can be used. The visual field area is set to bonding layer thickness × 40 μm in the width direction. The measurement conditions for the area analysis are as described above. The area ratio is calculated using the element map obtained by the area analysis. For the element map, the pinning size is set to 5×5 bit / point. When using image analysis software such as Image-J, binarization processing is performed. The concept of the binarization processing is as follows. First, let Sx be the area of the element x to be detected. Sx can be determined by Sx = ((number of pixels in the extraction region obtained by binarization of element x) / (total number of pixels in the image)) × 100. The area can be obtained for each of the elements x to be detected, which are changed to Ti, Si, N, and C respectively. For example, the area ratio of the Ti-Sn alloy can be obtained as follows. As described above, in the second composition region of the Cu-Sn alloy (first alloy 6), the Ti content is 0 atomic% or more and 25 atomic% or less. Therefore, regions with a Ti content of 25 atomic% or less are excluded. The element map is shown with luminance corresponding to the Ti concentration. This function can be used to exclude regions with a Ti content of 25 atomic% or less. The image of the element map from which regions with a Ti content of 25 atomic% or less have been excluded is binarized to measure the area of the Ti element and the area of the Si element. Let the area of the Ti-Sn alloy be S Sn-Ti , the area of the Ti element be S Ti , the area of the Si element be S Si , the area of the N element be S N , and the area of the C element be S C . The area of the Ti-Sn alloy is S Sn-Ti =S Ti -(S Si +S N +S CThis can be determined from the following: The Si present in the bonding layer is titanium silicide. The N (nitrogen) present in the bonding layer is titanium nitride. If the boundary between the silicon nitride substrate surface and the bonding layer is wavy, silicon nitride may be detected. Also, the C (carbon) present in the bonding layer is elemental carbon or titanium carbide. Ti S Si S N S C This can also be done by binarizing images that map only Ti, Si, N, and C, and then calculating using those images. The area ratio of the Cu-Sn alloy is S Cu-Sn Let's assume that. S Cu-Sn From the region where the Ti content is 0 atomic% to 25 atomic%, S Si S N S C This can be obtained by removing [a certain element]. The element Ti can be present in both Cu-Sn alloys and Ti-Sn alloys. A distinction between Cu-Sn alloys and Ti-Sn alloys can be made based on a Ti content of 25 atomic percent. The bonding layer 4 may contain carbon. The carbon present in the bonding layer 4 may be elemental carbon or a carbide. The addition of carbon allows for control of the fluidity of the bonding brazing material. This makes it easier to control the distribution of the Cu-Sn alloy within the bonding layer. Other materials present in the bonding layer 4 besides the Cu-Sn alloy include titanium nitride (TiN), Ti-Sn alloy, and titanium silicide. If carbon is present, titanium carbide (TiC) may also be present. Furthermore, the components constituting the bonding layer 4 may exist as elemental metals. Note that alloys and elemental metals can be distinguished from the electron diffraction pattern of a TEM.

[0021] The bonding layer 4 preferably contains titanium silicide particles 8 with a major axis of 0.5 μm or more and 6 μm or less. In a field of view of the bonding layer 4 = bonding layer thickness × width direction of 200 μm, the total area of ​​the titanium silicide particles 8 with a major axis of 0.5 μm or more and 6 μm or less is preferably 1% or more and 15% or less of the field of view. SEM images are used to measure the major axis of the titanium silicide particles 8. The major axis is defined as the distance between the two furthest points on the outer edge of the titanium silicide particles 8 visible in the magnified cross-section of the bonding layer 4. The titanium silicide particles 8 present in the bonding layer 4 can be identified using the mapping function included in the area analysis function of SEM-EDX. Specifically, Ti and Si are designated as specific elements, and the presence of these elements is visualized. Regions where both Ti and Si are present correspond to the titanium silicide particles 8. If titanium silicide particles 8 are present, it is preferable that 80% to 100% of the titanium silicide particles 8 are located within 1 μm of the Ti reaction layer 5. When the Ti reaction layer 5 or the Ti that did not become part of the Ti-Sn alloy reacts with the silicon nitride substrate, titanium silicide particles are formed. The presence of titanium silicide particles 8 near the Ti reaction layer 5 makes it easier for Cu and the first element to penetrate the grain boundaries of the titanium nitride particles. If the major axis of the titanium silicide particles 8 exceeds 6 μm, or if the area ratio exceeds 15%, the formation of the Ti reaction layer 5 may be insufficient.

[0022] The thickness of the bonding layer 4 is preferably between 5 μm and 60 μm. Within this range, it is easy to control the area ratio of the Cu-Sn alloy. The thickness of the bonding layer 4 is the distance from the boundary between the ceramic substrate 2 and the Ti reaction layer 5 to the boundary between the bonding layer 4 and the copper plate 3. The concentration (atomic %) of the first element at the boundary between the bonding layer 4 and the copper plate 3 is defined as the first concentration C1. The concentration (atomic %) of the first element in a region within the copper plate 3 10 μm away from the boundary between the bonding layer 4 and the copper plate 3 is defined as the second concentration C2. The ratio of the second concentration C2 to the first concentration C1, C2 / C1, is preferably 0.60 or less. Furthermore, the concentration (atomic %) of the first element in a region of the copper plate 3 located 20 μm away from the boundary between the bonding layer 4 and the copper plate 3 is defined as the third concentration C3. The ratio of the third concentration C3 to the first concentration C1, C3 / C1, is preferably 0.40 or less. When a pure copper plate is used as the copper plate 3, the second concentration C2 and the third concentration C3 represent the amount of diffusion of the first element into the copper plate 3. If Sn is used in bonding layer 4, the concentration of Sn will be used as the concentration of the first element. If In is used in bonding layer 4, the concentration of In will be used as the concentration of the first element. If both Sn and In are used in bonding layer 4, the sum of the concentrations of Sn and In will be used as the concentration of the first element. For example, if the bonding layer 4 contains a Cu-Sn alloy, the first concentration is C1 Sn , the second concentration is C2 Sn , the third concentration is C3 Sn This is how it is written. C2 Sn / C1 Sn ≤0.60 or C3 Sn / C1 Sn A value of ≤0.40 indicates that the diffusion of Sn into the copper plate is suppressed. By having first alloys 6 with different composition ratios within the bonding layer 4, the amount of diffusion of the first element into the copper plate 3 can be reduced. Furthermore, the diffusion distance of the first element from the boundary is preferably 50 μm or less. The diffusion region refers to the distance from the boundary to the point where the amount of Sn is 0 mass% (below the detection limit). Also, as will be described later, if a bonding method using a continuous furnace is used, the first concentration can be reduced to 8 atomic %% or less. The second concentration C2 and third concentration C3 in the copper plate 3 are analyzed by EDX. Line analysis is used for the analysis. By reducing the amount of Sn diffusing into the copper plate 3, the heat resistance of the copper plate 3 can be improved. For example, when Sn diffuses into the copper plate 3, a CuSn alloy is formed within the copper plate. CuSn alloys have a lower melting point than copper plates. Therefore, as the amount of CuSn alloy in the copper plate increases, the copper plate becomes more susceptible to deformation due to heat. This may reduce the TCT properties of the bonded body. Although Sn was used as an example here, the same applies to In. The above configuration allows for a reduction in the amount of voids in the bonding layer. By reducing the amount of Sn (or In) diffusion into the copper plate, the amount of voids in the bonding layer can be reduced to 0% or more and 3% or less by volume ratio. Ultrasonic testing (SAT) is used to calculate the amount of voids in the bonding layer. A probe for flaw detection is brought into contact with the surface of the bonded body 1, and ultrasonic waves are transmitted toward the bonding layer 4. From the received results of the reflected waves, voids present in the bonding layer can be examined. Furthermore, the volume ratio of the voids can be calculated from the received results. By reducing the amount of voids in the bonding layer, the bonding strength of the copper plate can be improved. The bonding strength is measured by a peel test. The bonding strength of the copper plate can be increased to 15kN / mm or more, and even to 25kN / mm or more.

[0023] The above-described bonded structure is suitable for ceramic circuit boards. Figure 4 is a schematic diagram showing an example of a ceramic circuit board according to an embodiment. In Figure 4, 10 is a ceramic circuit board, 11 is a circuit section, and 12 is a heat sink. The ceramic circuit board 10 shown in Figure 4 is manufactured by processing the copper plate 3 on the front side of the bonded body 1 into a circuit section 11 and the copper plate 3 on the back side into a heat sink 12. The copper plate 3 to which the circuit shape is given is used as the circuit section 11. In Figure 4, two circuit sections 11 are provided. However, the ceramic circuit board 10 according to this embodiment is not limited to this structure. The number and size of the circuit sections 11 can be changed as appropriate as needed. In addition, although the copper plate 3 on the back side is used as the heat sink 12 in Figure 4, the circuit structure may be provided on both sides of the copper plate 3. If necessary, a slanted shape may be provided on the side surface of the circuit section 11 or the side surface of the heat sink 12. If necessary, an overhang may be provided in the bonding layer 4 between the ceramic substrate 2 and the circuit section 11, extending beyond the side edge of the circuit section 11. An overhang may be provided in the bonding layer 4 between the ceramic substrate 2 and the heat sink 12, extending beyond the side edge of the heat sink 12. An etching process is preferred for creating the circuit structure and the inclined shape of the copper plate side surface.

[0024] The ceramic circuit board according to this embodiment is suitable for semiconductor devices. Figure 5 is a schematic diagram showing an example of a semiconductor device according to an embodiment. In Figure 5, 20 is a semiconductor device, 21 is a semiconductor element, and 22 is a lead frame. In the semiconductor device 20 shown in Figure 5, a semiconductor element 21 is mounted on one of two circuit sections 11. A lead frame 22 is connected to the other of the two circuit sections 11. Note that the semiconductor device 20 according to the embodiment is not limited to this structure. The number and size of the circuit sections 11, the number and size of the semiconductor elements 21, etc. can be changed as needed.

[0025] Next, a method for manufacturing the joined body according to the embodiment will be described. The manufacturing method is not limited as long as the joined body according to the embodiment has the above configuration. Below, an example of a method for obtaining a joined body with good yield will be described. First, prepare the ceramic substrate 2. Examples of ceramic substrate 2 include silicon nitride substrates, aluminum nitride substrates, aluminum oxide substrates, and argil substrates. Note that an argil substrate is a substrate formed by mixing aluminum oxide and zirconium oxide. As copper plate 3, a pure copper plate or a copper alloy plate can be used. The copper plate is preferably oxygen-free copper. Oxygen-free copper is copper with a purity of 99.96% by mass or higher, as specified in JIS-H-3100. Next, prepare the bonding brazing material. Preferably, the bonding brazing material contains 50 atomic% or more of Cu, 5 atomic% to 40 atomic% of Ti, 2 atomic% to 35 atomic% of the first element, and 0 atomic% to 12 atomic% of carbon. This is the ratio when the total of Cu, Ti, the first element, and C is 100 atomic%. Ti may be added as titanium hydride (TiH2). It is effective not to add Ag to the bonding brazing material.

[0026] It is preferable to investigate the properties of the brazing material used in the manufacture of the joint beforehand using DSC. The DSC curve of the brazing material is measured by setting the heating rate in the heating process to 20°C / min and the cooling rate in the cooling process to 20°C / min. DSC will be performed using a NETZSCH TGA-DSC simultaneous thermal analyzer STA449-F3-Jupiter or an instrument with equivalent performance. The measurement will be performed in an argon (Ar) flow after dropping an appropriate amount of brazing material into an alumina container. The measurement will be performed with the lid of the alumina container closed. It is necessary to prevent the brazing material from reacting with the atmosphere by performing the measurement in an Ar atmosphere. The amount dropped (mg) should be measured in advance using a balance. A sample of 15 mg or more should be used. In the heating process, the temperature was raised from room temperature to 950°C at a heating rate of 20°C / min. Next, a holding process was performed where the temperature was maintained at 950°C for 20 minutes. In the cooling process, the temperature was lowered from 950°C to room temperature at a cooling rate of 20°C / min. The temperature profile for which the DSC curve is derived consists of the heating process, the holding process, and the cooling process. Hereafter, the DSC curve of the cooling process at a cooling rate of 20°C / min may be referred to as the DSC curve of the cooling process. Furthermore, peaks were defined as those where the difference in heat flow was 0.02 mW / mg or more. If a first alloy 6 exists whose solidification point or phase transition point is between 400°C and 600°C, an exothermic peak will be detected in the DSC curve of the cooling process within the range of 400°C to 600°C. If multiple exothermic peaks are detected between 400°C and 600°C in the DSC curve of the cooling process, the temperature at which the largest peak appears will be considered the solidification point or phase transition point of the bonding layer 4.

[0027] Average particle size D of Cu powder, which is the raw material for wax. 50 The average particle size D of the Ti powder or TiH2 powder is preferably 12.0 μm or less, and more preferably 10.0 μm or less. 50 The average particle size D of the Sn powder or In powder is preferably 6.0 μm or less, and more preferably 4.0 μm or less. 50 The average particle size of the C powder is preferably 16.0 μm or less, and more preferably 14.0 μm or less. 50 The average particle size of the Ag powder is preferably 6.0 μm or less, and more preferably 4.0 μm or less. 50 The particle size is preferably 3.0 μm or less, and more preferably 2.0 μm or less. By controlling the particle size of the powder, the reaction of each powder can be made uniform. Average particle size of Cu powder D 50This refers to the average particle size D of Sn powder or In powder. 50 It is preferable that the particle size be smaller than the given size. As mentioned above, Cu and the first element form the base material of the brazing material composition. The first element has a lower melting point than Cu. By increasing the particle size of the Sn powder or In powder, the reaction between the Cu powder and the first element powder can be made uniform. As a result, even if the heating rate or cooling rate is increased, the ceramic substrate 2 and the copper plate 3 can be sufficiently bonded.

[0028] The process of joining a ceramic substrate and a copper plate is carried out using the bonding brazing material described above. The bonding brazing material is mixed with organic matter to prepare a brazing paste. The brazing paste is applied to the surface of the ceramic substrate 2 (or copper plate 3) to form a brazing paste layer. The copper plate 3 (or ceramic substrate 2) is placed on the brazing paste layer. The heat bonding process is carried out in a nitrogen atmosphere. A nitrogen atmosphere is an atmosphere with a nitrogen content of 70 vol% or more. Preferably, the nitrogen content of the nitrogen atmosphere is 70 vol% or more, and more preferably 85 vol% to 100 vol%. Other components in the nitrogen atmosphere include inert gas or air. Heat bonding in a nitrogen atmosphere can be carried out under various conditions such as atmospheric pressure, reduced pressure, or pressurized pressure.

[0029] In the heating step of the heat bonding process, the heating rate is set to 30°C / min or higher. The upper limit of the heating rate is not particularly limited, but is preferably 100°C / min or lower. If the heating rate is faster than 100°C / min, the bonding performance may decrease. For this reason, the heating rate is preferably 30°C / min or more and 100°C / min or less, and more preferably 40°C / min or more and 70°C / min or less. The bonding temperature is set to 750°C or higher. Preferably, the bonding temperature is 1000°C or lower. If the bonding temperature is higher than 1000°C, it will approach the melting point of copper (1085°C). As a result, the copper plate may deform. For this reason, the bonding temperature is preferably between 750°C and 1000°C, and more preferably between 800°C and 950°C. In the heat bonding process, the bonding temperature should be maintained for at least 10 minutes. The time during which the bonding temperature is maintained is called the heating and holding time. The heating and holding time is preferably between 10 minutes and 100 minutes. If the heating and holding time is less than 10 minutes, there may not be enough time for the brazing material to melt and solidify. If the heating and holding time is longer than 100 minutes, it may become difficult to control the distribution of the alloy within the bonded layer 4. After the heating and holding time is complete, a cooling process is performed. The cooling process is the process of cooling from the joining temperature to room temperature. The cooling rate is set to 30°C / min or higher. In conventional activated metal joining methods, the cooling rate was about 5°C / min. By using a joining brazing material having the DSC curve described above, joining becomes possible even if the cooling rate is increased. There is no particular upper limit to the cooling rate, but it is preferably 100°C / min or less. If it is faster than 100°C / min, the bonding performance may decrease. For this reason, the cooling rate is preferably 30°C / min or more and 100°C / min or less, and more preferably 30°C / min or more and 70°C / min or less. In addition, it is preferable to use a continuous furnace to increase the heating rate and cooling rate. A continuous furnace can perform heat treatment in a nitrogen atmosphere. Since it is not necessary to create a vacuum, the heating rate and cooling rate can be increased.

[0030] By increasing the cooling rate, the distribution of Cu-Sn alloy within the bonding layer 4 can be controlled. This is because rapid cooling after the bonding brazing material has melted makes it possible to form an alloy corresponding to the solidification point or phase change point. Furthermore, by allowing the presence of Ti that does not become part of the Ti reaction layer 5, it is possible to form Ti-Sn alloy and titanium silicide particles. Rapid cooling can suppress unwanted diffusion phenomena into the copper plate. The difference between the heating rate and the cooling rate is preferably 20°C / min or less. In other words, it is preferable that |heating rate - cooling rate| ≤ 20°C / min is satisfied. In the brazing material layer, a dissolution reaction and a solidification reaction occur when heated. These reactions occur in the heating process and the cooling process. By reducing the difference between the heating rate and the cooling rate, the stress caused by the reaction can be made uniform. This makes it possible to suppress defects such as warping. If necessary, the heating and joining process may be carried out while placing a weight on the joined body 1. The joined body 1 can be manufactured through the joining process described above. Furthermore, since the thermal stress of the joining layer 4 can be reduced, the warping of the joined body 1 can be reduced. The resulting bonded body 1 is etched to form a ceramic circuit board 10. If necessary, multiple pieces can be produced by scribing the bonded body 1.

[0031] (Examples) (Examples 1-8, Comparative Example 1) The bonding brazing materials shown in Tables 1 and 2 were prepared. Table 1 shows the particle size of the raw material powders, and Table 2 shows the composition ratios.

[0032] [Table 1]

[0033] [Table 2]

[0034] The bonding brazing material components from the examples and comparative examples were mixed with an organic binder to prepare brazing pastes. The DSC curves of each brazing paste were measured using a differential scanning calorimeter. For DSC analysis, a NETZSCH STA449-F3-Jupiter TGA-DSC simultaneous thermal analyzer was used. Measurements were performed in an Ar flow by dropping an appropriate amount of brazing material into an alumina container. The temperature program was set to a heating rate of 20°C / min, holding at 950°C for 20 minutes, and a cooling rate of 20°C / min. The temperature at which an exothermic peak was detected in the DSC curve of the cooling process was measured. Table 3 shows the temperature at which the largest exothermic peak appeared in the DSC curve of the cooling process between 400°C and 600°C.

[0035] [Table 3]

[0036] As can be seen from Table 3, for the bonding brazing material in the example, the exothermic peak temperature in the cooling process of the DSC curve was within the range of 400°C to 600°C. In contrast, in Comparative Example 1, the exothermic peak temperature exceeded 600°C. No exothermic peak was detected within the range of 400°C to 600°C. Furthermore, for the bonding brazing material in the example, an exothermic peak was also detected in the range of 600°C to 900°C. Next, silicon nitride substrates were prepared as ceramic substrates. A silicon nitride substrate with a thermal conductivity of 90 W / m·K, a three-point bending strength of 600 MPa, and dimensions of 300 mm (length) x 200 mm (width) x 0.32 mm (thickness) was designated as silicon nitride substrate 1. Another silicon nitride substrate with a thermal conductivity of 85 W / m·K, a three-point bending strength of 650 MPa, and dimensions of 300 mm (length) x 200 mm (width) x 0.25 mm (thickness) was designated as silicon nitride substrate 2. Copper plate 1 was made from oxygen-free copper measuring 300 mm in length, 200 mm in width, and 0.5 mm in thickness. Copper plate 2 was made from oxygen-free copper measuring 300 mm in length, 200 mm in width, and 0.8 mm in thickness. A 30 μm layer of brazing paste was applied to both sides of a ceramic substrate, and the copper plates were placed on each side. Next, a heat bonding process was carried out. The bonding atmosphere was standardized to a nitrogen atmosphere. The bonding conditions were set within the range of 850°C to 920°C for 30 to 50 minutes, and a continuous furnace was used. The heating rate and cooling rate were set to the conditions shown in Table 4. The difference between the heating rate and the cooling rate was calculated as |heating rate - cooling rate|.

[0037] [Table 4]

[0038] The bonded body was manufactured using the above process. The cross-section of the bonded layer of the obtained bonded body was observed to determine the presence or absence of Cu-Sn alloys with different composition ratios, the average grain size of titanium nitride in the Ti reaction layer, and the amount of Cu and Sn in the Ti reaction layer. Furthermore, if Cu-Sn alloys with different composition ratios were present, the presence or absence of a first Cu-Sn alloy with an Sn content of 3 to 9 atomic percent and a second Cu-Sn alloy with an Sn content of 10 to 30 atomic percent were investigated. We also investigated the area ratios of Cu-Sn alloys and Ti-Sn alloys. Furthermore, we examined the major axis and area ratio of titanium silicide. To calculate the area ratios, we used a method of binarizing the EDX elemental map using image processing software. The detailed method is as described above. The results are shown in Tables 5-8.

[0039] [Table 5]

[0040] [Table 6]

[0041] [Table 7]

[0042] [Table 8]

[0043] As can be seen from Table 5-8, the bonded body in the example met the favorable conditions. The Cu-Sn alloy formed the main component of the bonded layer. Furthermore, it was observed that the first Cu-Sn alloy and the second Cu-Sn alloy were intermetallic compounds. EDX point analysis was performed at 10 arbitrary locations within the Cu-Sn alloy region. Similarly, EDX point analysis was performed at 10 arbitrary locations within the Ti-Sn alloy region. The results, shown in the ternary phase diagram in Figure 3, all fell within the first composition region. Furthermore, the EDX point analysis results for the Cu-Sn alloy showed that the composition of Cu-Sn alloys between 80% and 100% was within the second composition region. The EDX point analysis results for the Ti-Sn alloy showed that the composition of Ti-Sn alloys between 80% and 100% was within the third composition region. In Table 8, the area ratio labeled "Other" represents regions where the Ti reaction layer, carbides, or metal components existed dissolved and separated in their individual components. The thickness of the Ti reaction layer in the bonded body according to the example was 1 μm or less. Furthermore, both TiN and Ti2N were observed in the Ti reaction layer. In contrast, no Cu-Sn alloys with different composition ratios were detected in Comparative Example 1. Although trace amounts of Cu-Sn alloy were observed in Comparative Example 1, no Cu-Sn alloys with different compositions were observed. This is thought to be because AgCu eutectic or AgSn was the main component of the bonding layer in Comparative Example 1. Next, 100 jointed bodies were manufactured for each example and comparative example. The joint strength and warpage of each were measured. The bonding strength was measured by a peel test. Specifically, a sample for the peel test was prepared for each example and comparative example. The sample consisted of a strip-shaped copper plate bonded to a ceramic substrate. In this process, one end of the copper plate was bonded so that it protruded from the ceramic substrate. The peel strength was measured by pulling the protruding copper plate vertically. Furthermore, the amount of warping was measured on the longer side of the joint. For joints with 90 or more pieces, cases where the amount of warping was 0.3 mm or less were classified as "best." For joints with 70 to 89 pieces, cases where the amount of warping was 0.3 mm or less were classified as "good." For joints where 31 or more pieces had a warping amount exceeding 0.3 mm, they were classified as "poor." The results are shown in Table 9.

[0044] [Table 9]

[0045] As can be seen from Table 9, the joint strength of the joint according to the example was equivalent to that of the joint according to Comparative Example 1, which used Ag-containing brazing material. Even when the size of the joint was increased to 200 mm or more, the amount of warping could be suppressed. Even when the heating rate and cooling rate were increased, the amount of warping could be suppressed. Therefore, it can be seen that the joint is suitable for mass production. In contrast, in Comparative Example 1, many joints with a warping amount exceeding 0.3 mm were produced. This is because Cu-Sn alloys with different composition ratios were not formed.

[0046] The amount of Sn in the copper plate of the bonded structures in the examples and comparative examples was investigated. The amount of Sn was measured by analyzing the cross-section of the bonded structure using EDX. The boundary between the bonded layer and the copper plate was defined by the method described above. The amount of Sn at the boundary between the bonded layer and the copper plate was defined as Sn-1, the amount of Sn at a location 10 μm away from the boundary as Sn-2, and the amount of Sn at a location 20 μm away from the boundary as Sn-3. Sn-2 / Sn-1 and Sn-3 / Sn-1 were calculated. We also checked whether the point furthest from the boundary in the region where Sn was detected was within 50 μm. Examples where it was within 50 μm were marked with "○", and examples where it exceeded 50 μm were marked with "×". The presence or absence of voids in the bonding layer was also investigated. The presence or absence of voids was determined by ultrasonic testing (SAT). A void volume ratio of 0% to 0.3% was marked "◎", 0.4% to 1% was marked "〇", 2% to 3% was marked "△", and 4% or more was marked "×". The results are shown in Table 10.

[0047] [Table 10]

[0048] As can be seen from Tables 9 and 10, the diffusion of Sn into the copper plate was suppressed in the joints according to the examples. Furthermore, the void area was also found to be small. In particular, in Examples 6 to 8, where the void area was reduced, the joint strength was high, at 25 kN / mm or more. In contrast, the comparative example showed a large amount of Sn diffusion into the copper plate and a large void area ratio.

[0049] Although several embodiments of the present invention have been illustrated above, these embodiments are presented as examples only and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. Modifications of these embodiments are included in the scope and spirit of the invention, as well as in the claims of the invention and its equivalents. Furthermore, the embodiments described above can be implemented in combination with each other. [Explanation of Symbols]

[0050] 1...Zygote 2…Ceramic substrate 3...Copper plate 4...Joining layer 5...Ti reaction layer 6…Cu-Sn alloy or Cu-In alloy 7…Ti-Sn alloy or Ti-In alloy 8...Titanium silicide particles 10…Ceramic circuit board 11...Circuit section 12...Heat sink

Claims

1. A step of preparing a bonding brazing material containing Cu, Ti, a first element selected from Sn and In (or two of them), and C, with the total amount of these elements being 100 atomic percent, Cu being 50 atomic percent or more, Ti being 5 atomic percent or more and 40 atomic percent or less, the first element being 2 atomic percent or more and 35 atomic percent or less, and carbon being 0 atomic percent or more and 12 atomic percent or less. The process of preparing the aforementioned bonding brazing material as a bonding brazing paste, A step of applying the bonding brazing paste to the surface of a ceramic substrate or copper plate, The steps include: placing a copper plate or ceramic substrate on the bonding brazing paste; A method for manufacturing a bonded body, comprising a heating bonding step of heating and bonding the ceramic substrate and the copper plate to obtain a bonded body, In the aforementioned heating and bonding process, the heating rate is 30°C / min or more and 100°C / min or less, the bonding temperature is 750°C or more and 1000°C or less, and the cooling rate is 30°C / min or more and 100°C / min or less. The resulting bonded body includes the ceramic substrate, the copper plate, and a bonding layer disposed between the ceramic substrate and the copper plate, formed by heating the bonding brazing paste. The aforementioned bonding layer is A Ti reaction layer containing titanium nitride or titanium oxide as the main component, A plurality of first alloys are located between the Ti reaction layer and the copper plate, each containing one or more selected from Cu-Sn alloys and Cu-In alloys, and having different Sn or In concentrations from each other. A method for manufacturing a composite body, including the above.

2. The method for manufacturing a bonded body according to claim 1, wherein the heating bonding step satisfies |heating rate - cooling rate| ≤ 20°C / min.

3. The method for manufacturing a bonded body according to claim 1 or claim 2, wherein the heating bonding step is carried out in a nitrogen atmosphere with a nitrogen content of 70 vol% or more.

4. The method for manufacturing a joined body according to any one of claims 1 to 3, wherein the heating and holding time for holding the joined body at the bonding temperature in the heating and bonding step is 10 minutes or more and 100 minutes or less.

5. The bonding layer further comprises a second alloy located between the Ti reaction layer and the copper plate. The second alloy contains one or more selected from Ti-Sn alloys and Ti-In alloys. A method for manufacturing a bonded body according to any one of claims 1 to 4, wherein, in the average value obtained by analyzing three regions of the bonding layer with a thickness × width of 40 μm, the total area of ​​the plurality of first alloys is greater than the total area of ​​the second alloy.

6. At least a portion of the plurality of first alloys is a Cu-Sn alloy, The second alloy is a Ti-Sn alloy, A method for manufacturing a bonded body according to claim 5, wherein at least a portion of the plurality of first alloys and the second alloy, as detected by EDX point analysis of the bonding layer, are located within the regions enclosed by (97, 3, 0), (60, 40, 0), (2, 40, 58), and (39, 3, 58) in the ternary phase diagram of Cu, Sn, and Ti.

7. The second alloy is a Ti-Sn alloy, The method for manufacturing a bonded body according to claim 6, wherein the second alloy detected by EDX point analysis of the bonded layer is within the region enclosed by (41, 23, 36), (24, 40, 36), (2, 40, 58), and (19, 23, 58) in the ternary phase diagram of Cu, Sn, and Ti.

8. The method for producing a bonded body according to claim 7, wherein the Ti content in one or more of the plurality of first alloys is 1 atomic percent or less.

9. A method for manufacturing a jointed body according to any one of claims 1 to 8 is performed, A method for manufacturing a ceramic circuit board, comprising etching the resulting bonded body to impart a circuit structure to the copper plate to obtain a ceramic circuit board.

10. A method for manufacturing a ceramic circuit board according to claim 9, comprising performing multiple moldings on the obtained ceramic circuit board.

Citation Information

Patent Citations

  • Bonding composition

    JP1993097532A

  • Ceramic circuit board

    JP1997283656A

  • Soldering method and super sonic sensor

    JP1998251074A

  • Ceramic-copper assembly and manufacturing method of the same

    JP2013211546A

  • Junction body and power module substrate

    JP2015043392A